1992
DOI: 10.1097/00006254-199210000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pregnancy Success in Repeated Miscarriage

Abstract: Factors that may have a bearing on subsequent pregnancy success or failure in patients with recurrent abortion were examined in 165 women with a history of three or more consecutive miscarriages in the first trimester. The overall success rate was 67.9%. Factors that were found to correlate significantly with success rate were length of abortion history, total number of abortions, interval from last miscarriage to present pregnancy, and whether there was any degree of subfertility. Logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Many authors have reported an increased risk of fetal death and spontaneous abortion with increasing maternal age, especially over 30 years, irrespective of previous obstetric history Cauchi et al, 1991;Lund et al, 2012;Bhattacharya et al, 2010).…”
Section: Age and Risk Of Miscarriagementioning
confidence: 99%
“…Many authors have reported an increased risk of fetal death and spontaneous abortion with increasing maternal age, especially over 30 years, irrespective of previous obstetric history Cauchi et al, 1991;Lund et al, 2012;Bhattacharya et al, 2010).…”
Section: Age and Risk Of Miscarriagementioning
confidence: 99%